Removal of cadmium from aqueous solution by optimized rice husk biochar using response surface methodology - Ameen Hezam Saeed, A. (Ain Shams University, 2022)
The removal of Cd (II) ions by rice husk biochar as adsorbent was evaluated through batch study. Activated biochar was prepared using the physicochemical activation method. Preparation was consisting of pre-impregnation of NaOH and nitrogen (N2) pyrolysis. The Influence of preparation parameters which were chemical impregnation (NaOH: RH), pyrolysis temperature, and pyrolysis time on biochar yield, cadmium removal rate, and adsorption capacity on cadmium ions was investigated. A quadratic model for correlating biochar preparation variables with biochar production, cadmium removal rate, and adsorption capability was built according to central composite design (CCD). The experimental results revealed that pyrolysis temperature and heating time are important factors that affect the yield of biochar and positively affect Cadmium's removal rate and adsorption capacity. The impregnation ratio positively impacted Cadmium removal and adsorption capacity, and it did not affect biochar yield. The optimal biochar was obtained using 458 â¦C temperature, 120 min reaction time, and 3 NaOH impregnation ratio, resulting in 34.5 of biochar yield, 72 of cadmium removal, and 17.8 mg/g of adsorption capacity on Cadmium. Â© 2021 THE AUTHORS